Morocco : Third Review under the Arrangement under the Precautionary and Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2016)
This paper reviews Morocco's economic performance under a program supported by a two-year Precautionary and Liquidity Line (PLL) arrangement. Macroeconomic conditions of Morocco have continued to improve, but challenges remain same. Continued reform implementation will be essential to strengthen macroeconomic buffers and promote higher and more inclusive growth. Sustained implementation of structural reforms will be critical to boost potential growth in the medium term. The authorities intend to continue to treat the current arrangement as precautionary, and are still assessing possible options regarding Morocco's exit strategy and the potential need for a successor arrangement. Overall, Morocco continues to meet the qualification criteria for a PLL arrangement.